Controllability characterization of switched DAEs. Issue 1 (21st October 2015) - Küsters, Ferdinand; Trenn, Stephan
Abstract We study controllability of switched differential algebraic equations (switched DAEs) with fixed switching signal. Based on a behavioral definition of controllability we are able to establish a controllability characterization that takes into account possible jumps and impulses induced by the switches. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)